Application Of Picture Media In Writing Descriptive Texts Using The Problem Based Learning (PBL) Model For Grade IV Elementary School Students - Wirnita; Yuni Okta Afriani; Nirwansyah (Journal Of Global Research Publications, 2024)
This research is motivated by the lack of descriptive text writing skills of students in high classes, namely grade IV of Elementary School. The purpose of the study was to describe the improvement of descriptive text writing skills in learning Indonesian through the application of image media in using the problem based learning (PBL) model in grade IV of SDN 55 Air Pacah, Padang City. This type of research is Classroom Action Research (CAR). The research instruments used were teacher activity observation sheets, student activity observation sheets, and student writing skill assessment sheets. The percentage of teacher activity obtained in Cycle I was 80% and increased in Cycle II with a percentage of 92.5%. The average observation of student activities in Cycle I was 72.5% and increased in Cycle II with an average of 85%. The completion of student writing skill learning outcomes in Cycle I was 44% with an average learning outcome of 62, increasing to 84% in Cycle II with an average learning outcome of 78. Based on the results of this assessment, it can be concluded that the Problem Based Learning (PBL) model can improve students' descriptive text writing skills